Spatiotemporal changes of the habitat quality and the human activity intensity and their correlation in mountainous cities - Han, Huiqing; Zhang, Yingjia; Liu, Yue; Yu, Xin; Wang, Junwen (Journal of Environmental Engineering and Landscape Management, 2022)
As the urbanization is being rapidly boosted, the urban habitat quality has been significantly disturbed by human activities through land use, which highly affects the urban ecological environment and sustainable development of social economy. However, the change characteristics of the habitat quality and human activities in different topographic gradients in rapidly urbanized mountainous cities remain unclear. Accordingly, Guiyang in China, is selected as the representative of typical mountain cities. The change characteristics of the habitat quality, the human activity intensity and their correlation in mountainous cities from 2000 to 2020, are analyzed using the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, as well as the ArcGIS software based on the remote sensing interpretation data in 2000, 2010 and 2020. The results demonstrate that the overall habitat quality in Guiyang decreased by 0.0304, while the human activity intensity increased by 0.0287 from 2000 to 2020. The amount of changes of the habitat quality and the human activity intensity in Guiyang from 2010 to 2020, are higher than those from 2000 to 2010. The amount of changes of the habitat quality and the human activity intensity in Guiyang decreases with the increase of the slope. The central and southern parts of Guiyang are the highlight areas with a significant decline of habitat quality and significant increase of human activity intensity. The areas with an increased habitat quality and decreased human activity intensity are sporadically distributed. A significant negative correlation is reported between the change of the habitat quality and human activity intensity in Guiyang. In addition, a prominent spatial heterogeneity is identified in the local indicators of the spatial association (LISA) map. The significant increase in the artificial land and the decrease in the natural land as affected by the rapid urbanization, act as crucial factors leading to the decline of the habitat quality and the increase in the human activity intensity in mountainous cities.